2019
DOI: 10.1080/00207233.2019.1674584
|View full text |Cite
|
Sign up to set email alerts
|

Microbial contamination of main contact surfaces of Automated Teller Machines from Metropolitan Area of Porto

Abstract: Automated Teller Machines (ATM) are likely to be contaminated with various microorganisms because of their contact with the hands of many users daily. The main objective of this study was to investigate ATMs as a potential source of bacterial contamination. This study was conducted in the Metropolitan Area of Porto, in which 50 swab samples were cultured on selective media. Some isolates were identified based on colonial, morphological and biochemical characteristics. Susceptibility to several antibiotics was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…A total of seven (7) bacterial species were recovered from interfaces in this study, which included skin commensals (Staphylococcus and Micrococcus), environmental bacteria (Serratia and Pseudomonas) and enteric bacteria (Salmonella and Klebsiella) ( Table 5 ). Barbosa et al, [ 45 ] and Aquino et al, [ 46 ] in their study also discovered almost the same range of bacteria and this time it was found associated with multidrug resistance. The health risks associated with the majority of these bacteria are well documented [ 47 ].…”
Section: Discussionmentioning
confidence: 68%
“…A total of seven (7) bacterial species were recovered from interfaces in this study, which included skin commensals (Staphylococcus and Micrococcus), environmental bacteria (Serratia and Pseudomonas) and enteric bacteria (Salmonella and Klebsiella) ( Table 5 ). Barbosa et al, [ 45 ] and Aquino et al, [ 46 ] in their study also discovered almost the same range of bacteria and this time it was found associated with multidrug resistance. The health risks associated with the majority of these bacteria are well documented [ 47 ].…”
Section: Discussionmentioning
confidence: 68%
“…It has been observed that antibiotic susceptibility of bacterial isolates was multiple drug resistance for all strains. The data of present study are according to Barbosa [12], that reported the bacteria risk of spreading antibiotic-resistant bacteria through contact with ATM machines and should not be neglected, in terms of impact on public health.…”
Section: Discussionmentioning
confidence: 86%
“…The data from the present study demonstrated that the evaluated ATMs are subject to contamination by pathogenic bacteria, as occurs in other countries. A study carried out by Barbosa et al [12] in the Metropolitan Area of Porto (Portugal) showed that 50 ATMs were contaminated with Enterobacteriaceae, E. coli, Enterococci, Staphylococcus coagulase positive and Listeria spp.…”
Section: Prevalence Of Gram-positive and Gram-negative In Atmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Colonization of e-banking facilities by pathogenic organisms has been reported as a potential vehicle for their transmission [10,11,12]. Microorganisms found to contaminate fomites are known to persist on environmental surfaces for varying periods of time ranging from hours to months.…”
Section: Introductionmentioning
confidence: 99%